2021
DOI: 10.3390/ani11051316
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Country Approach to Improve the Test-Day Prediction of Dairy Cows’ Dry Matter Intake

Abstract: We predicted dry matter intake of dairy cows using parity, week of lactation, milk yield, milk mid-infrared (MIR) spectrum, and MIR-based predictions of bodyweight, fat, protein, lactose, and fatty acids content in milk. The dataset comprised 10,711 samples of 534 dairy cows with a geographical diversity (Australia, Canada, Denmark, and Ireland). We set up partial least square (PLS) regressions with different constructs and a one-hidden-layer artificial neural network (ANN) using the highest contribution varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This shows that indeed these predictions are possible to some extent, but also that ignoring systematic effects of, for example, MY and BW did not reduce the accuracy of the predictions of DMI. Brand et al (2021) achieved better predictions of pregnancy status from milk IR spectra with a machine learning approach than with PLS, but Tedde et al (2021) found very similar DMI prediction accuracies using either PLS regression or machine learning. This suggests that improvement of predictions using milk IR spectra using machine learning compared with PLS regression is trait dependent.…”
Section: Discussionmentioning
confidence: 96%
“…This shows that indeed these predictions are possible to some extent, but also that ignoring systematic effects of, for example, MY and BW did not reduce the accuracy of the predictions of DMI. Brand et al (2021) achieved better predictions of pregnancy status from milk IR spectra with a machine learning approach than with PLS, but Tedde et al (2021) found very similar DMI prediction accuracies using either PLS regression or machine learning. This suggests that improvement of predictions using milk IR spectra using machine learning compared with PLS regression is trait dependent.…”
Section: Discussionmentioning
confidence: 96%
“…While individual cow 'walk-over' weighing systems already exist and are in place on some commercial farms, their adoption within the UK is very limited, and this situation looks unlikely to change for the foreseeable future. Nevertheless, research has attempted to predict individual cow BW on the basis of days-in-milk, milk yield, parity and milk mid-infrared spectrum [27]. If this approach is successful then individual cow BW values could be predicted with sufficient accuracy to improve precision within individual cow feeding systems.…”
Section: Cow Intake and Performancementioning
confidence: 99%
“…Moreover, whereas milk is an important source of nutritive elements for humans, its fine composition—or, more specifically, composition changes—is important to know, as it mirrors the metabolic and health status of the animal. This explains why some indicators related to metabolism and animal health, such as energy balance or intake ( Ho et al, 2020 ), BW ( Tedde et al, 2021a ), DMI ( Tedde et al, 2021b ), acetonemia ( Grelet et al, 2016 ), pregnancy status ( Delhez et al, 2020 ), SARA ( Mensching et al, 2021 ), fertility ( Ho et al, 2019 ), lameness ( Bonfatti et al, 2020 ), and so on, can be derived from the milk FT-MIR spectrum. Another important topic is the environmental footprint of milk production.…”
mentioning
confidence: 99%